The Effects of Probiotics, Prebiotics and Synbiotics on Glycemic Control in Diabetic Patients: A Narrative and Meta-Analysis Study - Dorsa Ghafouri (International Journal of Nutrition Sciences, 2025)
One of the most important therapeutic fields in management of persistent and progressive illnesses that substantially affects global health burden is glycemic control. Recently, probiotics and prebiotics have emerged as complementary therapies in diabetes, aiming the composition and function of gut microbiota. These microbiome-modulating agents can improve metabolic health through an enhanced glucose homeostasis and the insulin sensitivity. The key focus of the present review is a research into the effect of probiotics, prebiotics, and synbiotics on metabolic health in diabetic patients, concerning glucose metabolism, inflammation, and insulin sensitivity. A literature review was conducted between 2010 and 2024 using databases of Science Direct, Springer, Google Scholar, and PubMed. Based on findings, such interventions were shown to provide new strategies to improve glycemic control in patients with diabetes through inflammatory mechanisms, gut-derived metabolites, and other metabolic pathways. In addition, these nutraceuticals can present broader benefits beyond simple glycemia control, such as modifying lipid level and reducing systemic inflammation; while both of which arecrucial for management of metabolic syndrome and the prevention of complications from diabetes. While the evidence seems promising at this point, this review is a call to the need for further long-term studies to establish the sustained efficacy and safety of such microbiome-targeting therapies. Therefore, more researches would be needed to fully establish the therapeutic potential of these therapies and to further develop their clinical use for treatment of diabetes.